Effect of Composition Growing Media and Nutrient Solution for Growth and Yield Pakcoy (Brassica rapa L. Chinensis) in Hydroponic Substrate - Koesriharti, Koesriharti; Istiqomah, Annisa (Plantropica: Journal of Agricultural Science, 2016)
Pakcoy (Brassica rapa L. Chinensis) is a vegetable plant that can cultivated in hydroponics system. On hydroponic substrate cultivation, compotition of growing media and nutrient solution are the factors that affect growing plant and yield determinant. However, the prices of nutrient solution relatively expensive become obstacle for people. Therefore, alternative nutrient solution is required. The purpose of the research is to know the suitable compotition of growing media and nutrient solution on growth and yield pakcoy in hydroponic substrate. This research conducted in Tegalweru village Dau Malang from February until July 2016. The research was using factorial randomized block design with 3 replications. First factor were composition of growing media consist of 3 levels: (M1) sand and rice husk 1:1, (M2) sand and cocopeat 1:1, and (M3) sand, rice husk and cocopeat 1:1:1. Second factor were nutrient solution consisting of 5 levels: (P0) AB Mix 100%, (P1) T. diversifolia liquid manure 25% + cow liquid manure 75%, (P2) T. diversifolia liquid manure 50% + cow liquid manure 50%, (P3) cow liquid manure 50% + AB Mix 50%, and (P4) T. diversifolia liquid manure 25% + cow liquid manure 25% + AB Mix 50%. The result of this research showed that using composition of growing media M1 had higher result to lenght of plant and stem diameter than growing media M2. Using composition of the growing media M1 showed higher result to number of leaf, than growing media M3. Nutrient solution P3 and P4 significantly affect to lenght of plant higher than nutrient solution P0.Â